Evaluation of remelting low-fluxing ferrotitanium slag as a potential refractory raw material: Thermal characteristics and stability. Issue 8 (15th April 2022) - Li, Yichong; Zhao, Huizhong; Ma, Jiuhong; Wang, Yu; Zhang, Han; Yu, Jun; Feng, Li; liu, Yanli
Abstract: To effectively promote the utilization of metallurgical waste slag, studies on the characteristics and stability of waste slag are essential for waste reuse. Ferrotitanium slag is a byproduct of smelting ferrotitanium with thermite reduction. Low-fluxing ferrotitanium slag (LFS) is the main type of dumping slags produced by ferrotitanium smelting. In this study, an electric arc furnace was used to prepare remelting LFS (RLFS) for homogenization and impurity removal. The characteristics and thermal stability of RLFS as a refractory raw material were characterized. The thermal stability of RLFS was tested under different working conditions. A phase-structure transition mechanism of RLFS particles was established according to the thermal stability test and thermodynamic calculations. The Al2 O3 content in RLFS exceeded 80%, and RLFS had lower thermal conductivity than brown corundum, but a similar thermal expansion coefficient. The results show that RLFS is a suitable substitute for corundum raw material; the thermal stability test results show that RLFS was susceptible to crack propagation in an oxidizing environment above 1280 °C. The findings of this research provide suggestions for the utilization of RLFS to improve the application stability of refractory products using recycled raw materials.